Rescue on turtle beach - Marlin, Jen (Marlin, Jen. Wind riders, 2021)
After discovering Wind Rider, an abandoned magical sailboat, Max and Sofia arrive on a beach in Hawaii where, with new friend Laila, they rescue newly-hatched sea turtles. Includes facts about sea turtles.